Pengaruh Pengetahuan Anggota Dewan Perwakilan Rakyat Tentang Anggaran Terhadap Pengawasan Keuangan Daerah (APBD) dengan Partisipasi Masyarakat dan Akuntabilitas Publik Sebagai Variabel Moderating (Studi Empiris Pada DPRD Kota Jambi) - Panika Friantama; Mukhzarudfa Mukhzarudfa (Jurnal Akuntansi & Keuangan Unja, 2018)
The purpose of this research are (1) to know the influence of budgeting knowledge to budgeting control (2) to know the influence of public participation on the relationship between budgeting knowledge and budgeting control (3) to know the influence of public Accountability on the relationship between budgeting knowledge and budgeting control. This research is a survey by distributing questionnaires directly to the sample. The population in this research are legislative assembly at provincial (DPRD) in Kota Jambi. The result of this research indicated that (1) budgeting knowledge influence to budgeting control (2) public participation influence to relationship between budgeting knowledge and budgeting control (3) public Accountability influence to relationship between budgeting knowledge and budgeting control. Keyword: Budgeting knowledge, public participation, public Accountability, Budgeting Control.